Efficacy and safety of intravenous alteplase for unknown onset stroke on prior antiplatelet therapy: post hoc analysis of the EOS individual participant data - Shiomi, Yuma; Miwa, Kaori; Jensen, Märit; Inoue, Manabu; Yoshimura, Sohei; Kamogawa, Naruhiko; Fukuda-Doi, Mayumi; Ma, Henry; Ringleb, Peter A.; Wu, Ona; Schwamm, Lee H; Davis, Stephen M; et al. (International journal of stroke, 2025)
Background: The effects of intravenous alteplase in patients with prior antiplatelet therapy (APT) remain controversial. We aimed to assess the efficacy and safety of imaging-based intravenous alteplase in patients with unknown onset stroke with prior APT. - Methods: Data from randomized controlled trials comparing alteplase with placebo/standard care in patients with unknown onset acute ischemic stroke from the Evaluation of Unknown Onset Stroke Thrombolysis (EOS) individual patient data meta-analysis collaboration were analyzed. Favorable outcome was defined as a modified Rankin Scale score of 0-1 at 90 days post-stroke. Safety outcomes included symptomatic intracranial hemorrhage (sICH) at 22-36 h and 90-day mortality. - Results: Overall, 780 patients had available baseline data on prior APT. Compared with the no prior APT group (n = 523), the prior APT group (n = 257) was older (72 vs. 66 years) and had a higher prevalence of vascular risk factors. There was no interaction between prior APT and treatment effects of alteplase (p for interaction = 0.23). In the prior APT patients, 55/125 (45%) patients in the alteplase group and 39/132 (30%) patients in the control group had a favorable outcome (adjusted odds ratio [aOR], 2.07 [95% confidence interval, 1.18-3.64]). The rates of sICH and mortality in the alteplase and control groups were 5.6% and 0.8% (aOR, 7.78 [0.94-63.37]) and 6.5% and 6.1% (aOR, 1.12 [0.38-3.36]), respectively. In the no prior APT patients, 136 patients (50%) in the alteplase group and 112 patients (45%) in the control group had a favorable outcome (aOR, 1.39 [0.94-2.05]). Safety outcomes were not significantly different between the groups (sICH: 3 [1.1%] vs. 1 [0.4%]; mortality: 13 [4.9%] vs. 3 [1.2%]). - Conclusions: Alteplase has consistent efficacy regardless of prior APT in patients with unknown onset stroke. In addition, prior APT does not significantly increase the risk of sICH or mortality.